Granulation Of Porous Materials with Phase Change Material (PCM) - Bien, Tomasz (Budownictwo i Architektura / Civil and Architectural Engineering, 2021)
The paper describes the research on the method of production of granulated phase-change materials (PCM) used in construction industry for the accumulation of thermal energy. As mineral materials for the granules preparation zeolite from fly ash Na-P1 and natural diatomite dust were used which were impregnated with paraffinic filtration waste and granulated using a combined granulation method. Obtained granules were characterized using X-ray diffraction (XRD), scanning electron microscopy (SEM), nitrogen adsorption/desorption isotherm, and differential scanning calorimetry (DSC). Mechanical strength of the materials was determined in a “drop strength” test. Performed analyses revealed that mineral composition and micromorphology of the diatomite and zeolite granules were varied, with zeolite granules having higher mechanical strength.